Tuberculous pericarditis mimicking multiple tumors in pericardial effusion. Issue 5 (May 2019) - Li, Caie; Zhao, Qiming; Wu, Xiangyang; Yu, Jing
Tuberculosis is still the leading cause of pericardial disease in developing nations. A definite diagnosis of tuberculosis is usually relatively difficult, especially when its manifestations are not typical. We report a 19-year-old man who presented with chest obstruction, shortness of breath, edema of the lower extremities, and mild fever for 14 days. The manifestations of tuberculosis pneumonia were not typical, except for a small high-density shadow in the left upper lung field near the pleura, with a small amount of pleural effusion on chest computed tomography. The tuberculin skin test, acid-fast stain of sputum and pericardial effusion, and bacterial culture showed negative results. Echocardiography showed three free-floating irregular masses in a large amount of pericardial effusion. The masses and exudates were removed by pericardiectomy. The masses were composed of hyperplastic granulation tissue and dead tissue without a normal architecture, mixed with numerous caseous substances, which confirmed the diagnosis of tuberculous pericarditis. This is a unique report of a patient who presented with tuberculous pericarditis with multiple solid masses in a large amount of pericardial effusion, without typical clinical manifestations of tuberculosis.